Body mass index, atopy, and allergic diseases - Afnita Lestary; Lily Irsa; Tiangsa Sembiring; Rita Evalina; Meiviliani Sinaga (Paediatrica Indonesiana, 2016)
Background Prevalence of atopy, allergic diseases, and obesity are increasing. Atopy is an individu and/or familial tendency to sensitization in response to ordinary exposure to allergens. Studies on association of BM I with atopy and allergic diseases in children were limited, with inconclusive results. Objective To assess associations of BM I with atopy and allergic diseases in chidren. Methods A cross-sectional was conducted in school children aged 6-12 years in Lhokseumawe City, Aceh, June 2012. Children were assessed for BMI, skin prick test, and International Study of Asthma and Allergies in Childhood (ISAAC) questionnaire. Statistical analyses included Chi-square, Fisher exact, and logistic regression. Results The subjects consisted of 137 (85.6%) normoweight, 12 (7.5%) overweight, and 11 (6.9%) obesity. Skin prick test results were positive in 44 (27.5%) and negative in 116 (72.5%) subjects. Allergic manifestations were allergic rhinitis (AR) 17 (10.6%), bronchial asthma 6 (3.8%), and atopic dermatitis (AD) 3 (1.9%). There was significant association of obesity with atopy, compared with normoweight (OR=3.78; 95%CI 1.08 to 13.19; P=0.037), but no significant association found when family history of atopy also assesed. There was significant association of obesity with bronchial asthma (OR=9.92; 95%CI 1.46 to 67.18; P=0.004) and AR (OR=6.49; 95%CI 1.64 to 25.66; P=0.015), compared with normoweight children. Significant association of overweight with atopy and allergic disease were not found. Conclusion Obese children are more likely to have atopy, bronchial asthma, and allergic rhinitis, but overweight and normoweight children are not.